Perspectives on Academic Writing in European Higher Education: Genres, Practices, and Competences - Otto Kruse (Universitat Politècnica de València, 2013)
Academic writing in European higher education is a little explored field hidden behind fifty major language and fifty national educational systems of which it is part. The article aims at developing a perspective for studying the diversity of writing in Europe and finding a shared language for analyzing student writing. The article recaps baselines theories for the teaching of writing and reports on three important European writing traditions. The main part of the paper is devoted to three foundational conceptions for writing: The role of genres in understanding student writing, the function of writing practices for the organization of student writing and the meaning of writing competences for the teaching of writing.